2022
DOI: 10.1016/j.tsc.2022.100998
|View full text |Cite
|
Sign up to set email alerts
|

How adolescents develop and implement their ideas? On self-regulation of creative action

Abstract: This study explores how adolescents regulate their activity while working on creative projects. A large sample (N = 739) of Polish adolescents reported on their most creative, complex project conducted within the last year and answered retrospectively framed self-regulation items related to this specific activity. Exploratory and confirmatory factor analyses demonstrated a consistent pattern of self-regulation, capturing pre-task self-regulatory strategies (obstacles expectations, uncertainty acceptance), duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 106 publications
1
54
0
Order By: Relevance
“…One reason to expect such a relationship is the lower subjective cognitive load that complex tasks induce among more creatively self-efficacious people (Redifer et al, in press). Additionally, given their confidence and experience, they might have a more pragmatic and organized approach to such problems and feel less stressed and helpless when faced with them (Zielińska et al, 2022; Zielińska, Lebuda, & Karwowski, in press).…”
Section: Creativity As a Decision: Creative Behavior As Agentic Actio...mentioning
confidence: 99%
“…One reason to expect such a relationship is the lower subjective cognitive load that complex tasks induce among more creatively self-efficacious people (Redifer et al, in press). Additionally, given their confidence and experience, they might have a more pragmatic and organized approach to such problems and feel less stressed and helpless when faced with them (Zielińska et al, 2022; Zielińska, Lebuda, & Karwowski, in press).…”
Section: Creativity As a Decision: Creative Behavior As Agentic Actio...mentioning
confidence: 99%
“…This is perfectly in line with conceptualizations of creative self-concept as a surface characteristic of a creative personality (Lebuda et al, 2021). Moreover, given higher malleability of the creative self-concept and its predictive effect on creative effort and action (Zielińska, Lebuda, Ivcevic, & Karwowski, 2022), the possibility to support and enrich creative self-concept gains particular relevance (Mathisen & Bronnick, 2009; Meinel et al, 2019). We propose that future work explore the possibility of developing educational interventions that might shape both creative confidence (i.e., creative self-efficacy) and the perceived importance of creativity; namely, creative personal identity.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has showed that people have a natural bias against creativity over feasibility because of uncertainty [ 15 , 52 ]. As such, children may select different types of ideas to reduce uncertainty in the implementation phase [ 67 ]. Future research should aim to investigate these underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%